2011
DOI: 10.1007/s00296-011-2077-6
|View full text |Cite
|
Sign up to set email alerts
|

T helper cell subsets in arthritis and the benefits of immunomodulation by 1,25(OH)2 vitamin D

Abstract: The prevalence of vitamin D deficiency has been shown to be increased in many of the common arthritides. Importantly, vitamin D has significant immunomodulatory effects in addition to its role in calcium homoeostasis. Both aspects of its function have a major bearing on joint disease whether as part of an inflammatory arthritis or from wear and tear. While the exact mechanisms still require clarification, there is now compelling evidence that the hormonally active 1,25-dihydroxycholecalciferol vitamin D can re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 80 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…Low vitamin D levels are associated with higher circulating proinflammatory cytokines in HIV positive patients with increased CD4+ counts in those treated with vitamin D . In rheumatoid diseases there are data to support that vitamin D reduces proinflammatory T‐cell subsets TH 1 and TH 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low vitamin D levels are associated with higher circulating proinflammatory cytokines in HIV positive patients with increased CD4+ counts in those treated with vitamin D . In rheumatoid diseases there are data to support that vitamin D reduces proinflammatory T‐cell subsets TH 1 and TH 17 …”
Section: Discussionmentioning
confidence: 99%
“…We use the 20-60 nmol/L category as the baseline as this was the largest group. BMI (kg/m 2 ) was classified using the standard classification system defined by the World Health Organization of underweight (<18.5), normal (18.5-25), overweight (25)(26)(27)(28)(29)(30) and obese (301). 23 Cases were interviewed about whether they had diabetes and about their smoking habits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though PG alone did not modify cytokine production, animals that received VitD3+PG association produced significantly lower cytokine levels after specific stimulation. The therapeutic effect of VitD3 is already well documented in experimental arthritis [112,113]; however, our results constitute the first direct in vivo assessment of its tolerogenic potential. Recently, it was demonstrated that the association of VitD3 with myelin oligodendrocyte glycoprotein-derived [93].…”
Section: Discussionmentioning
confidence: 82%
“…, IL17 to provide anti-microbial immunity at epithelial and mucosal barriers) [ 31 ] in order to polarize the CD4 + T-cells responses toward a more regulatory Th2 ( i.e. , IL2 which activate humoral-mediated immunity by the production of neutralizing antibodies by B-cells to induce protection against extracellular pathogen) [ 32 ] or Threg phenotypes [ 14 , 33 ]. These two last phenotypes are considered key components of VitD capacity to suppress Th1-driven autoimmunity responses [ 28 , 33 ].…”
Section: Immunomodulating Role Of Vitd In Host Protectionmentioning
confidence: 99%